The Effect of Fermerherbafit Encapsulation Supplementation on Feed Intake and Final Body Weight of Male Sentul Chickens - Akbar Satria Bahari; Imron Adi Saputro; Ning Iriyanti; Bambang Hartoyo (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2025)
This study aimed to evaluate the supplementation of encapsulated fermerherbafit on feed intake and final body weight of male Sentul chickens. The study used 60 male white Sentul chickens, housed individually in battery cages and raised for 30 days. A Completely Randomized Design (CRD) was employed, consisting of five treatment groups with four replications each. The treatments were as follows: R0: 0% fermerherbafit supplementation (control), R1: 2% non-encapsulated fermerherbafit supplementation, R2: 2% encapsulated fermerherbafit supplementation, R3: 4% encapsulated fermerherbafit supplementation, and R4: 6% encapsulated fermerherbafit supplementation. Data were analyzed using analysis of variance (ANOVA). The average daily feed intake of male Sentul chickens ranged from 75.22 g/bird/day to 78.45 g/bird/day, with an overall average of 77.00 g/bird/day. The final body weight ranged from 1,417 g/bird to 1,540 g/bird, with an overall average of 1,469 g/bird. The results of the variance analysis indicated that fermerherbafit supplementation had no statistically significant effect on feed intake or final body weight of male Sentul chickens. The study concluded that supplementation of encapsulated fermeherbafit up to a level of 6% in the feed did not significantly affect feed intake and has not yet been able to increase the final body weight of Sentul male chickens. Keywords: Sentul chickens, supplementation, fermerherbafit, feed comsumption, body weights